upaya Presiden Jokowi Dodo dalam menghadapi penolakan ekspor komuditas CPO (Crude Palm Oil) oleh Uni Eropa Pada Tahun 2017-2020 - Vioneida Pranggadia L.A; Alfian Hidayat; Khairur Rizki (Indonesian Journal of Global Discourse, 2021)
Since the European Union (EU) began implementing the Renewable Economic Directive (RED) policy, it mainly talks about banning Indonesian Crude Palm Oil (CPO). Therefore, various efforts have been made by the Indonesian Government, in this case by President Joko Widodo. The purpose of this research is to explore the role of Joko Widodo and the state in dealing with EU’s Indonesian CPO ban. This research uses two theories; the theory of mercantilism analyzes the role of the state in managing its economy, while rational choice theory analyzes President Joko Widodo as the decision-maker in considering Indonesia’s policies. This research is a qualitative-descriptive research, which uses library research as its secondary data collection technique. The research also uses Miles and Huberman’s interactive model of data analysis. The results of this research concluded that Indonesia implemented industrialization policies and opened new markets, both domestic and international markets as a strategy to oppose the CPO ban by the European Union. Some of the industrialization programs include; B20, B30 to B100 programs, processing CPO to become new products, and opening up global markets in several countries that are considered to have great opportunities as export destinations for Indonesia’s CPO. This is due to the high consumption and demand for global and domestic palm oil, especially in the years 2017-2020.